2010
DOI: 10.1007/s10584-010-9959-6
|View full text |Cite|
|
Sign up to set email alerts
|

Exposure of developing countries to sea-level rise and storm surges

Abstract: An increase in sea surface temperature is strongly evident at all latitudes and in all oceans. The scientific evidence to date suggests that increased sea surface temperature will intensify cyclone activity and heighten storm surges. The paper assesses the exposure of (coastal) developing countries to sea-level rise and the intensification of storm surges. Geographic Information System (GIS) software is used to overlay the best available, spatially-disaggregated global data on critical exposed elements (land, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(95 citation statements)
references
References 17 publications
2
84
0
3
Order By: Relevance
“…Note that we did explore the use of the Dynamic Interactive Vulnerability Assessment (DIVA) model, but were unable to obtain the data. We examined data from Dasgupta et al [34], which incorporate the DIVA results, but because they rely heavily on SRTM data we found that they under estimate the areas at low elevations.…”
Section: Coastal West Africa Data Integrationmentioning
confidence: 99%
“…Note that we did explore the use of the Dynamic Interactive Vulnerability Assessment (DIVA) model, but were unable to obtain the data. We examined data from Dasgupta et al [34], which incorporate the DIVA results, but because they rely heavily on SRTM data we found that they under estimate the areas at low elevations.…”
Section: Coastal West Africa Data Integrationmentioning
confidence: 99%
“…Some studies combine the effects of climate change, through increased eustatic sea level, and storm surge to model potential future inundation scenarios (Dasgupta et al, 2011;Kleinosky et al, 2007). The concept of minimum inundation increment is applicable in both cases, to the sea-level rise increments and to the storm surge heights used in the study.…”
Section: Minimum Increment Of Inundationmentioning
confidence: 99%
“…affected by a given water level increase, oftentimes due to sea-level rise and/or storm surges (Dasgupta et al, 2009;Dasgupta et al, 2011;Demirkesen et al, 2007;Ericson et al, 2006;Kleinosky et al, 2007;Li et al, 2009;McGranahan et al, 2007;Najjar et al, 2000;Neumann et al, 2010;Rowley et al, 2007;Schneider and Chen, 1980;Small and Nicholls, 2003;Titus and Richman, 2001;Titus et al, 1991;Weiss et al, 2011;Wu et al, 2002;Wu et al, 2009). …”
mentioning
confidence: 99%
“…For economic exposure, the input is often expressed in terms of gross domestic product (GDP), interpreted as a proxy of wealth for risk assessment. (2,(16)(17)(18)(19)(20)(21)(22)(23)(24) However, census data are based on administrative units; this prevents a direct integration of wealth maps with other physical and environmental data (e.g., flood depth and inundation area, land cover/land use, elevation, climate, soil, vegetation data), which are usually only available at a spatially explicit grid-cell level, and with spatial distribution patterns that do not conform to administrative boundaries. (25) There is, however, a strong demand for economic data that are independent from enumeration and administrative areas.…”
Section: Introductionmentioning
confidence: 99%